Flexible flow guide ring, preparation method and silicon carbide crystal growth method applying flexible flow guide ring

By using flexible guide rings made of materials such as tantalum carbide, tungsten carbide, molybdenum carbide, niobium carbide, and zirconium carbide, the problems of easy cracking of graphite guide rings and uneven growth of silicon carbide crystals are solved, and the growth of high-quality silicon carbide crystals is achieved.

CN120649143APending Publication Date: 2025-09-16JIANGSU CHAOXINXING SEMICON CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510772417.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-11
Publication Date
2025-09-16

AI Technical Summary

Technical Problem

Existing graphite guide rings are prone to cracking at high temperatures, resulting in uneven growth of silicon carbide crystals and the appearance of crystal defects such as dislocations, microtubes, hexagonal voids and cracks.

Method used

The flexible guide ring is made of materials such as tantalum carbide, tungsten carbide, molybdenum carbide, niobium carbide, and zirconium carbide. It is formed by high-temperature carbonization treatment. Combined with powder metallurgy and plastic forming processes, the guide ring with high thermal expansion coefficient and good flexibility is prepared, and is coated with zirconia ceramic coating to improve stability.

Benefits of technology

The risk of cracking of the guide ring is reduced, the uniformity and quality of silicon carbide crystal growth are improved, the occurrence of crystal defects is reduced, and the crystal purity and crystallization quality are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005443331510000111
    Figure BDA0005443331510000111
  • Figure HDA0005443331520000011
    Figure HDA0005443331520000011
Patent Text Reader

Abstract

The invention relates to the technical field of semiconductor materials, and particularly discloses a flexible flow guide ring, a preparation method and a silicon carbide crystal growth method applying the flexible flow guide ring. The flexible flow guide ring comprises any one or more of tantalum carbide, tungsten carbide, molybdenum carbide, niobium carbide and zirconium carbide. The preparation method of the flexible flow guide ring comprises the following steps: placing a flexible flow guide ring blank in heat treatment equipment containing silicon carbide powder or carbon powder, vacuumizing, filling argon, carbonizing, and obtaining the flexible flow guide ring after carbonization is finished. The silicon carbide crystal growth method using the flexible flow guide ring comprises the following steps: assembling the flexible flow guide ring and a crucible containing silicon carbide seed crystals and silicon carbide powder, transferring the crucible to a single crystal growth furnace after the assembly is completed, growing the silicon carbide crystals by using a PVT method, and obtaining the high-quality silicon carbide crystals after the growth is completed. The problems of crystal defects and flow guide ring cracking in the growth process of the silicon carbide crystal can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semiconductor materials, in particular to a flexible guide ring and a preparation method thereof, and a silicon carbide crystal growth method using the flexible guide ring. Background Art

[0002] Silicon carbide (SiC) is a wide-bandgap semiconductor material with many excellent physical and chemical properties. For example, its thermal conductivity and electron mobility are much higher than those of silicon, making it a very promising third-generation semiconductor material. Currently, the physical vapor transport (PVT) method is mainly used to produce high-quality SiC crystals. When using the PVT method, a flow ring is required to promote the growth of SiC crystals. However, different flow rings have a significant impact on the quality of SiC crystals.

[0003] Currently, graphite flow rings are commonly used. While their structure is relatively stable during the high-temperature PVT process, the material experiences significant thermal stress, which can lead to cracking. Furthermore, conventional flow rings can experience localized oversaturation or undersaturation, resulting in uneven gas deposition on the SiC crystal growth surface. This leads to poor SiC crystal growth uniformity and the appearance of crystal defects such as dislocations, microtubes, hexagonal voids, and cracks. Summary of the Invention

[0004] In order to reduce the problems of crystal defects and guide ring cracking during the growth of silicon carbide crystals, the present application provides a flexible guide ring and a preparation method and a silicon carbide crystal growth method using the flexible guide ring.

[0005] In the first aspect, the present application provides a flexible guide ring, which adopts the following technical solution:

[0006] A flexible guide ring comprises any one or more of tantalum carbide, tungsten carbide, molybdenum carbide, niobium carbide and zirconium carbide.

[0007] By adopting the above technical solution, materials such as tantalum carbide, tungsten carbide, molybdenum carbide, niobium carbide, and zirconium carbide will expand in volume during the high-temperature process of the PVT method, making the structure of the flexible guide ring loose, which helps to reduce the thermal stress inside the material, thereby reducing the risk of cracking of the flexible guide ring. Moreover, the flexible guide ring of the present application is a non-graphite structure and has no risk of carbon wrapping defects. The flexible guide ring can guide the gas flow in the silicon carbide crystal growth area, and by reducing the phenomenon of local oversaturation or undersaturation of the reaction gas, the reaction gas is deposited on the growth surface of the silicon carbide crystal in a more uniform manner, thereby improving the uniformity of silicon carbide crystal growth and reducing crystal defects such as microtubes, hexagonal voids, and cracks. In addition, the flexible guide ring can improve the flow state of the gas and the temperature distribution in the crystal growth zone, thereby reducing dislocations during the growth of silicon carbide crystals.

[0008] In a second aspect, the present application provides a method for preparing a flexible guide ring, which adopts the following technical solution:

[0009] A method for preparing a flexible guide ring comprises the following steps: placing a flexible guide ring blank in a heat treatment device containing silicon carbide powder or carbon powder, evacuating the device, filling the device with argon, and carbonizing the device at a chamber pressure of 3-9 mbar and a temperature of 1600-2000°C for 60-80 hours. After the carbonization is completed, a flexible guide ring is obtained; the flexible guide ring blank comprises any one or more of tantalum, tungsten, molybdenum, niobium, and zirconium.

[0010] By adopting the above technical solution, the metal elements such as tantalum, tungsten, molybdenum, niobium, and zirconium in the flexible guide ring blank react with carbon to form carbides. These carbides have a high thermal expansion coefficient at high temperatures, and therefore can expand in volume at high temperatures. Metal elements such as tantalum, tungsten, molybdenum, niobium, and zirconium themselves have good ductility and plasticity, and can still maintain flexibility after forming carbides. Moreover, the high-temperature treatment performed in the above-mentioned temperature and pressure range in this application helps to further promote a more uniform and dense organizational structure within the material. Therefore, the above-mentioned method can improve the flexibility and plasticity of the material.

[0011] In a specific embodiment, the flexible guide ring blank comprises tantalum, niobium and zirconium in a mass ratio of 1:(0.6-1.2):(0.2-0.5).

[0012] By adopting the above technical solution, the present applicant has discovered that the flexible guide ring blank made from tantalum, niobium, and zirconium in the above mass ratio ultimately produces a flexible guide ring with superior flexibility. This is likely because, under the above ratio, tantalum, niobium, and zirconium can form intermetallic compounds. The intermetallic compounds work synergistically with the carbides formed by tantalum, niobium, and zirconium, allowing the flexible guide ring to quickly disperse internal stress during thermal expansion, further improving its flexibility and helping to reduce cracking caused by stress concentration.

[0013] In a specific embodiment, the flexible guide ring blank is prepared as follows:

[0014] Tantalum, niobium, and zirconium are mixed in proportion and ball-milled to obtain mixed metal powder;

[0015] Mixed metal powders are added to a die and forged into a ring-shaped structure;

[0016] The annular structure is made into a flexible guide ring blank by spin forming.

[0017] By employing this technical solution, the ball milling process allows for thorough mixing of metal powders such as tantalum, niobium, and zirconium, improving material uniformity. This helps form a more consistent microstructure during the subsequent forging and spinning processes, thereby enhancing the flexibility of the flexible guide ring. By combining powder metallurgy with plastic forming, production efficiency can be significantly improved. The ball milling, forging, and spinning process steps are easily automated and mass-produced, thereby reducing production costs.

[0018] In a specific embodiment, the flexible flow guide ring blank further includes lanthanum or cerium.

[0019] By adopting the above technical solution, lanthanum and cerium can enhance the thermal stability of the flexible guide ring, so that under high temperature conditions, the flexible guide ring can maintain better structural and performance stability and is less likely to deform or fail.

[0020] In a specific embodiment, the surface of the flexible guide ring blank is pre-cleaned, zirconium oxide powder is sprayed onto the surface of the flexible guide ring blank through a high-temperature plasma flame to form a ceramic coating, and then the flexible guide ring blank is placed in a heat treatment device containing silicon carbide powder or carbon powder.

[0021] By adopting this technical solution, the thermal expansion coefficients of the zirconia ceramic coating and the flexible guide ring are well matched. Furthermore, the zirconia ceramic material itself has excellent thermal shock resistance. Therefore, the flexible guide ring can maintain stable performance under rapid temperature fluctuations, reducing the risk of cracking or spalling. Furthermore, the ceramic coating has a high surface finish and a low coefficient of friction, which can reduce frictional resistance during operation of the flexible guide ring, improving its operating efficiency and reliability.

[0022] In a third aspect, the present application provides a method for growing silicon carbide crystals using a flexible guide ring, which employs the following technical solutions:

[0023] A method for growing silicon carbide crystals using a flexible guide ring comprises the following steps: assembling the flexible guide ring with a crucible containing silicon carbide seed crystals and silicon carbide powder; after the assembly is completed, transferring the crucible to a single crystal growth furnace; growing silicon carbide crystals using a PVT method; and obtaining high-quality silicon carbide crystals after the growth is completed.

[0024] By adopting the above technical solution, the introduction of a flexible guide ring helps to optimize the temperature field and airflow distribution during the growth of silicon carbide crystals, thereby reducing crystal growth dislocations or crystal defects such as microtubes, hexagonal voids, cracks, and improving the purity and crystal quality of the crystals.

[0025] In a specific embodiment, before assembling the flexible guide ring with the crucible containing the silicon carbide seed crystal and the silicon carbide powder, the following pretreatment is performed:

[0026] Cleaning the surface of the flexible guide ring in advance, and applying a light-absorbing coating on the surface of the flexible guide ring;

[0027] A laser beam is directed toward the surface of the flexible guide ring, and continuous laser shock treatment is performed on the flexible guide ring. After the laser shock treatment, the surface of the flexible guide ring is cleaned and the light-absorbing coating is removed, thereby completing the pretreatment.

[0028] By adopting this technical solution, the light-absorbing coating helps the flexible guide ring absorb the laser beam better, enhancing the effectiveness of laser shock processing. Laser shock processing can produce a high density of dislocations and residual compressive stresses on the material surface, refine the material's surface grains, optimize the microstructure, and further enhance the overall performance of the flexible guide ring.

[0029] In summary, this application has the following beneficial effects:

[0030] 1. The present application adopts a flexible guide ring including any one or more of tantalum carbide, tungsten carbide, molybdenum carbide, niobium carbide, and zirconium carbide, which will expand in volume during the high-temperature process of the PVT method, helping to reduce the risk of cracking of the flexible guide ring.

[0031] 2. The preparation method of the flexible guide ring of the present application helps to further promote a more uniform and dense organizational structure inside the material and improve the flexibility and plasticity of the material.

[0032] 3. The silicon carbide crystal growth method using a flexible guide ring of the present application helps to optimize the temperature field and airflow distribution during the growth of silicon carbide crystals, thereby reducing crystal growth dislocations or crystal defects such as microtubes, hexagonal voids, and cracks, and improving the purity and crystal quality of the crystals. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a schematic diagram of the structure of the flexible guide ring and the gas flow direction inside the growth crucible in Example 1 of the present application.

[0034] 1. Growth chamber; 2. Heating unit; 3. Growth crucible; 4. Silicon carbide seed crystal; 5. Flexible guide ring; 6. Assembly step; 7. Silicon carbide powder. DETAILED DESCRIPTION

[0035] The following is combined with Figure 1 , Examples and Comparative Examples further illustrate this application in detail.

[0036] Example

[0037] Example 1

[0038] This embodiment provides a method for growing silicon carbide crystals using a flexible guide ring, comprising the following steps:

[0039] like Figure 1 As shown, the flexible guide ring 5 is an annular structure, and the inner ring diameter at one end of the flexible guide ring 5 is smaller than the inner ring diameter at the other end.

[0040] The single crystal growth furnace houses a growth chamber 1, which contains a heating unit 2 and a growth crucible 3. The inner wall of the crucible 3 is provided with an assembly step 6. The flexible guide ring 5 has its inner ring end with the smaller diameter facing upward. Silicon carbide seed crystals 4 and silicon carbide powder 7 are located within the crucible 3. The silicon carbide powder 7 is located at the bottom of the crucible, while the silicon carbide seed crystals 4 are located at the top.

[0041] The flexible guide ring 5 and the growth crucible 3 containing the silicon carbide seed crystal 4 and the silicon carbide powder 7 are connected in accordance with Figure 1 After assembly, the growth crucible 3 is transferred to the growth chamber 1 of the single crystal growth furnace. The growth chamber 1 is evacuated and then filled with argon. The pressure of the growth chamber 1 is raised to 450mbar, and the growth crucible 3 is heated to 2350℃ and maintained in this state for 2 hours. The argon inlet flow rate is then adjusted to 100ml / min. Within 1.5 hours, the pressure in the growth chamber 1 is reduced from 450mbar to 60mbar, and the pressure is maintained at 60mbar for 1 hour. The pressure in the growth chamber 1 is then reduced from 15mbar to 2mbar within 120 hours. Inert argon gas is then filled into the furnace to a pressure of 500mbar, and the growth process is stopped. Maintaining this pressure, the temperature of the growth crucible 3 is reduced from 2350℃ to room temperature within 30 hours to obtain high-quality silicon carbide crystals.

[0042] The flexible guide ring 5 is prepared according to the following preparation method:

[0043] Tantalum metal is ball-milled to obtain metal powder.

[0044] Metal powder is added to a die and forged into a ring-shaped structure.

[0045] The annular structure is made into a flexible guide ring 5 blank by spin forming.

[0046] The flexible guide ring 5 green body is placed in a growth crucible 3 containing silicon carbide powder 7. The growth crucible 3 is then transferred to a single crystal growth furnace. After the single crystal growth furnace is evacuated, nitrogen is introduced into the chamber of the single crystal growth furnace. The chamber temperature is then increased to 3 mbar and 1600°C. These pressure and temperature conditions are then maintained for 60 hours to complete carbonization, yielding a flexible guide ring 5 comprising tantalum carbide.

[0047] Example 2

[0048] The only difference between this embodiment and embodiment 1 is that, in the flexible guide ring 5 prepared as follows, an equal amount of niobium metal is used to replace tantalum metal, thereby obtaining a flexible guide ring 5 comprising niobium carbide.

[0049] Example 3

[0050] The only difference between this embodiment and embodiment 1 is that, in the flexible guide ring 5 prepared as follows, an equal amount of zirconium metal is used to replace tantalum metal, thereby obtaining a flexible guide ring 5 comprising zirconium carbide.

[0051] Example 4

[0052] The only difference between this embodiment and embodiment 1 is that, in the flexible guide ring 5 prepared as follows, an equal amount of tungsten metal is used to replace tantalum metal, thereby obtaining a flexible guide ring 5 comprising tungsten carbide.

[0053] Example 5

[0054] The only difference between this embodiment and embodiment 1 is that, in the flexible guide ring 5 prepared as follows, an equal amount of molybdenum metal is used to replace tantalum metal, thereby obtaining a flexible guide ring 5 comprising molybdenum carbide.

[0055] Example 6

[0056] This embodiment differs from Example 1 only in that tantalum is replaced with a mixture of equal amounts of tantalum, niobium, and zirconium in a weight ratio of 1:0.5:0.6. In the preparation method for the flexible guide ring 5, tantalum, niobium, and zirconium are mixed and ball-milled to produce a mixed metal powder. The mixed metal powder is then placed in a mold and forged into a ring-shaped structure. The ring-shaped structure is then formed into a flexible guide ring 5 blank through spin forming.

[0057] Example 7

[0058] This embodiment differs from Example 1 only in that tantalum is replaced with a mixture of equal amounts of tantalum, niobium, and zirconium in a weight ratio of 1:0.6:0.5. In the preparation method for the flexible guide ring 5, tantalum, niobium, and zirconium are mixed and ball-milled to produce a mixed metal powder. The mixed metal powder is then placed in a mold and forged into a ring-shaped structure. The ring-shaped structure is then formed into a flexible guide ring 5 blank through spin forming.

[0059] Example 8

[0060] This embodiment differs from Example 1 only in that tantalum metal is replaced with a mixture of equal amounts of tantalum, niobium, and zirconium in a weight ratio of 1:0.9:0.35. In the preparation method for the flexible guide ring 5, tantalum, niobium, and zirconium are mixed and ball-milled to produce a mixed metal powder. The mixed metal powder is then placed in a mold and forged into a ring-shaped structure. The ring-shaped structure is then formed into a flexible guide ring 5 blank through spin forming.

[0061] Example 9

[0062] This embodiment differs from Example 1 only in that tantalum is replaced with a mixture of equal amounts of tantalum, niobium, and zirconium in a weight ratio of 1:1.2:0.2. In the preparation method for the flexible guide ring 5, tantalum, niobium, and zirconium are mixed and ball-milled to produce a mixed metal powder. The mixed metal powder is then placed in a mold and forged into a ring-shaped structure. The ring-shaped structure is then formed into a flexible guide ring 5 blank through spin forming.

[0063] Example 10

[0064] This embodiment differs from Example 1 only in that tantalum is replaced with a mixture of equal amounts of tantalum, niobium, and zirconium in a weight ratio of 1:1.4:0.1. In the preparation method for the flexible guide ring 5, tantalum, niobium, and zirconium are mixed and ball-milled to produce a mixed metal powder. The mixed metal powder is then placed in a mold and forged into a ring-shaped structure. The ring-shaped structure is then formed into a flexible guide ring 5 blank through spin forming.

[0065] Example 11

[0066] This embodiment differs from Example 1 only in that tantalum is replaced with a mixture of equal amounts of tantalum, niobium, zirconium, and lanthanum in a weight ratio of 1:0.9:0.35:0.2. In the preparation method for the flexible guide ring 5, tantalum, niobium, zirconium, and lanthanum are mixed and ball-milled to produce a mixed metal powder. The mixed metal powder is then placed in a mold and forged into a ring-shaped structure. The ring-shaped structure is then formed into a flexible guide ring 5 blank through spin forming.

[0067] Example 12

[0068] This embodiment differs from Example 1 only in that tantalum metal is replaced with a mixture of equal amounts of tantalum, niobium, zirconium, and cerium in a weight ratio of 1:0.9:0.35:0.2. In the preparation method for the flexible guide ring 5, tantalum, niobium, zirconium, and cerium are mixed and ball-milled to produce a mixed metal powder. The mixed metal powder is then placed in a mold and forged into a ring-shaped structure. The ring-shaped structure is then formed into a flexible guide ring 5 blank through spin forming.

[0069] Example 13

[0070] The only difference between this embodiment and embodiment 1 is that, in the preparation method of the flexible guide ring 5, the surface of the flexible guide ring 5 blank is pre-cleaned, zirconium oxide powder is sprayed onto the surface of the flexible guide ring 5 blank through a high-temperature plasma flame flow to form a 10 μm thick ceramic coating, and then the flexible guide ring 5 blank is placed in a growth crucible 3 containing silicon carbide powder 7.

[0071] Example 14

[0072] This embodiment differs from Example 1 only in the following method for preparing the flexible guide ring 5: The flexible guide ring 5 blank is placed in a growth crucible 3 containing silicon carbide powder 7. The growth crucible 3 is then transferred to a single crystal growth furnace. The single crystal growth furnace is evacuated, and then nitrogen is introduced into the chamber of the single crystal growth furnace. The chamber temperature is then increased, the pressure in the chamber being adjusted to 6 mbar, and the temperature being adjusted to 1800°C. These pressure and temperature conditions are then maintained for 70 hours to complete carbonization, thereby obtaining a flexible guide ring 5 comprising tantalum carbide.

[0073] Example 15

[0074] This embodiment differs from Example 1 only in the following method for preparing the flexible guide ring 5: The flexible guide ring 5 blank is placed in a growth crucible 3 containing silicon carbide powder 7. The growth crucible 3 is then transferred to a single crystal growth furnace. The single crystal growth furnace is evacuated, and then nitrogen is introduced into the chamber of the single crystal growth furnace. The chamber temperature is then increased, the pressure in the chamber being adjusted to 9 mbar, and the temperature to 2000°C. These pressure and temperature conditions are then maintained for 80 hours to complete carbonization, thereby obtaining a flexible guide ring 5 comprising tantalum carbide.

[0075] Comparative Example

[0076] Comparative Example 1

[0077] The only difference between this comparative example and Example 1 is that, in the flexible guide ring prepared as follows, an equal amount of nickel metal is used to replace tantalum metal, thereby obtaining a flexible guide ring containing nickel carbide.

[0078] Comparative Example 2

[0079] The only difference between this comparative example and Example 1 is that in the silicon carbide crystal growth method using the flexible guide ring, a graphite guide ring of the same specification is used to replace the flexible guide ring.

[0080] Performance testing

[0081] For Examples 1-15 and Comparative Examples 1-2, the following performance tests were performed:

[0082] After the silicon carbide crystal growth is completed, observe whether there are cracks on the surface of the flexible guide ring or graphite guide ring. If no cracks are observed, record it as no cracks. If the number of cracks observed is 1-2, record it as very few cracks. If the number of cracks observed is 3-4, record it as a few cracks. If the number of cracks observed is greater than 4, record it as a lot of cracks.

[0083] The prepared silicon carbide crystals were inspected for crystal defects such as dislocations, micropipes, hexagonal voids, and cracks. If no dislocations, micropipes, hexagonal voids, or cracks were detected, the crystal was recorded as defect-free. If any one of these defects, such as dislocations, micropipes, hexagonal voids, or cracks, was detected, the crystal was recorded as minimally defective. If any two of these defects, such as dislocations, micropipes, hexagonal voids, or cracks, were detected, the crystal was recorded as slightly defective. If three or more of these defects, such as dislocations, micropipes, hexagonal voids, or cracks, were detected, the crystal was recorded as heavily defective.

[0084] The test results are shown in Table 1.

[0085] Table 1

[0086]

[0087] Combining Examples 1-5 and Comparative Examples 1-2 and Table 1, it can be seen that Comparative Example 1 uses a flexible guide ring containing nickel carbide. After the growth of the silicon carbide crystal is completed, a small amount of cracks appear on the surface of the flexible guide ring, and a small amount of defects appear in the prepared silicon carbide crystal. Comparative Example 2 uses a graphite guide ring. After the growth of the silicon carbide crystal is completed, a large number of cracks appear on the surface of the graphite guide ring, and a large number of defects appear in the prepared silicon carbide crystal. After the growth of the silicon carbide crystal is completed, the flexible guide rings of Comparative Examples 1-5 all have very few cracks on the surface, and the prepared silicon carbide crystals all have very few defects. This shows that the use of the flexible guide rings of Examples 1-5 can reduce the problems of crystal defects and guide ring cracking during the growth process of silicon carbide crystals.

[0088] In combination with Examples 1, 6-13 and Table 1, it can be seen that compared to Example 1, the flexible guide rings of Examples 7-9 and 11-13 did not show cracks after the silicon carbide crystal growth was completed, the silicon carbide crystals prepared in Examples 7-9 showed very few defects, and the silicon carbide crystals prepared in Examples 11-13 showed no defects. However, the flexible guide rings of Examples 6 and 10 showed very few cracks after the silicon carbide crystal growth was completed, and the prepared silicon carbide crystals showed very few defects. This shows that the flexible guide ring prepared by using a flexible guide ring blank including tantalum, niobium and zirconium in a mass ratio of 1: (0.6-1.2): (0.2-0.5) can further reduce the cracking problem, and the addition of lanthanum or cerium can reduce the growth defects of silicon carbide crystals.

[0089] Combining Examples 1, 14-15, and Table 1, it can be seen that, compared to Example 1, the flexible guide rings of Examples 14-15 exhibited significantly fewer cracks after the silicon carbide crystals were grown, and the resulting silicon carbide crystals exhibited significantly fewer defects. This indicates that, within the process conditions of Examples 1 and 14-15, the flexible guide rings produced were able to reduce the occurrence of crystal defects and guide ring cracking during the silicon carbide crystal growth process.

[0090] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A flexible guide ring, characterized in that: Including any one or more of tantalum carbide, tungsten carbide, molybdenum carbide, niobium carbide, and zirconium carbide.

2. A method for preparing a flexible guide ring according to claim 1, characterized in that: The method comprises the following steps: placing a flexible guide ring blank in a heat treatment device containing silicon carbide powder or carbon powder, evacuating the device, filling the device with argon gas, and carbonizing the device at a chamber pressure of 3-9 mbar and a temperature of 1600-2000° C. for 60-80 hours. After the carbonization is completed, a flexible guide ring is obtained; the flexible guide ring blank comprises any one or more of tantalum, tungsten, molybdenum, niobium, and zirconium.

3. The method for preparing a flexible guide ring according to claim 2, characterized in that: The flexible guide ring blank comprises tantalum, niobium and zirconium in a mass ratio of 1:(0.6-1.2):(0.2-0.5).

4. The method for preparing a flexible guide ring according to claim 3, characterized in that: The flexible guide ring blank is prepared as follows: Tantalum, niobium, and zirconium are mixed in proportion and ball-milled to obtain mixed metal powder; Mixed metal powders are added to a die and forged into a ring-shaped structure; The annular structure is made into a flexible guide ring blank by spin forming.

5. The method for preparing a flexible guide ring according to claim 3, characterized in that: The flexible guide ring blank further comprises lanthanum or cerium.

6. The method for preparing a flexible guide ring according to claim 2, characterized in that: The surface of the flexible guide ring blank is cleaned in advance, zirconium oxide powder is sprayed onto the surface of the flexible guide ring blank through a high-temperature plasma flame flow to form a ceramic coating, and then the flexible guide ring blank is placed in a heat treatment device containing silicon carbide powder or carbon powder.

7. A method for growing silicon carbide crystals using the flexible guide ring according to claim 1, characterized in that: The method comprises the following steps: assembling a flexible guide ring with a crucible containing silicon carbide seed crystals and silicon carbide powder; after the assembly is completed, transferring the crucible to a single crystal growth furnace; growing silicon carbide crystals using a PVT method; and obtaining high-quality silicon carbide crystals after the growth is completed.

8. The method for growing silicon carbide crystals using a flexible guide ring according to claim 7, wherein: Before assembling the flexible guide ring with the crucible containing silicon carbide seed crystals and silicon carbide powder, the following pretreatment is performed: Cleaning the surface of the flexible guide ring in advance, and applying a light-absorbing coating on the surface of the flexible guide ring; A laser beam is directed toward the surface of the flexible guide ring, and continuous laser shock treatment is performed on the flexible guide ring. After the laser shock treatment, the surface of the flexible guide ring is cleaned and the light-absorbing coating is removed, thereby completing the pretreatment.